Results at the top : using gender intelligence to create breakthrough growth - Annis, Barbara, 1954-; Nesbitt, Richard, 1955- (Wiley, 2017)
Whether you're building your leadership team from scratch or trying to transform long-established norms for a competitive advantage today, this book wastes no space with blame for the current state of women leaders and goes straight to the immediate steps you can take to change it. --